THE ASSESSMENT OF BASIC TECHNICAL PARAMETERS OF THE COOLING SYSTEM OF THE LOCOMOTIVE DISK BRAKE - Biloborodova, I. M.; Osenin, Yu. I.; Sosnov, I. I. (Science and Transport Progress, 2009)
In the article a thermal (constructive) calculation of the liquid-air recuperative heat exchanger is executed. Its purpose was an estimation of the areas of heat-exchange surfaces and the consumption of heat carriers necessary for dissipation of thermal energy generated by a locomotive disk brake.